A Multifluorination Strategy Toward Wide Bandgap Polymers for Highly Efficient Organic Solar Cells. (26th January 2023) - Chen, Jinming; Li, Dongyan; Su, Mingbin; Xiao, Yonghong; Chen, Hui; Lin, Man; Qiao, Xiaolan; Dang, Li; Huang, Xiao‐Chun; He, Feng; Wu, Qinghe
Abstract: Creating new electron‐deficient unit is highly demanded to develop high‐performance polymer donors for non‐fullerene organic solar cells (OSCs). Herein, we reported a multifluorinated unit 4, 5, 6, 7‐tetrafluoronaphtho[2, 1‐b : 3, 4‐b′]dithio‐phene (FNT) and its polymers PFNT‐F and PFNT‐Cl. The advantages of multifluorination: (1) it enables the polymers to exhibit low‐lying HOMO (≈−5.5 eV) and wide band gap (≈2.0 eV); (2) the short interactions (F⋅⋅⋅H, F⋅⋅⋅F) endow the polymers with properties of high film crystallinity and efficient hole transport; (3) well miscibility with NFAs that leads to a more well‐defined nanofibrous morphology and face‐on orientation in the blend films. Therefore, the PFNT‐F/Cl : N3 based OSCs exhibit impressive FF values of 0.80, and remarkable PCEs of 17.53 % and 18.10 %, which make them ranked the best donor materials in OSCs. This work offers new insights into the rational design of high‐performance polymers by multifluorination strategy. Abstract : An electron‐deficient tetrafluoronaphthodithiophene (FNT) was created to construct a family of PFNT‐F/Cl polymers for organic solar cells. The PFNT‐F/Cl‐based OSCs exhibit impressive FF values of 0.80, and remarkable PCEs of 17.53 % and 18.10 %, suggesting multifluorinated polymers are promising donor materials for non‐fullerene OSCs.